Extent and Background Factors of Physical and Mental Disability in Bangladesh - Sultana, Amena; Gulshan, Jahida (Dhaka University Journal of Science, 2015)
The extent of disability in Bangladesh in recent time has been examined and the potential background factors causing different types of disability have been identified. The data on disability in Bangladesh was taken from Sample Vital Registration System (SVRS), 2010 collected by Bangladesh Bureau of Statistics. Chi-square test of association showed that type of disability varies significantly with respect to area, sex, division and religion. Age has no significant association with disability. A trichotomous logistic regression model presented the relationship between different background factors and type of disability. The model shows that the disability rate is higher among urban people as compared to rural people. The disability rate in Barisal, Dhaka, Khulna and Rajshahi are significantly higher than Sylhet. The male are more likely to be mentally disabled than female. Both physical and mental disability is higher among non muslims as compared to Muslims. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21962 Dhaka Univ. J. Sci. 62(1): 55-58, 2014 (January)